Cooperative design, visualization, and engineering : 13th International Conference, CDVE 2016, Sydney, NSW, Australia, October 24-27, 2016, Proceedings /: 13th International Conference, CDVE 2016, Sydney, NSW, Australia, October 24-27, 2016, Proceedings. (2016) - Unknown
No abstract available